A Clarion Call for Bridging the Educational Death Valley in Indian Higher Education - Sen, Dr. Payel; Singh, Dr. Raj (The journal of contemporary issues in business and government, 2021)
Since the turn of the millennium India’s Higher Education (HE) system is challenged by the compulsions of sudden and significant transformations spurred by globalization and information revolution. In line with the global trends the field of HE in India is constantly evolving and rapidly expanding making the country home to the largest number of HE institutions in the world with student enrolments at the third largest, next only to USA and China. Exponential expansion and diversification of the HE sector since the beginning of the 21st century is unprecedented. And, the rapidly growing involvement of the private sector in HE sector in the recent decades is stark. This is driven by the need to succeed in the new knowledge economy and to gain economic competitiveness and higher productivity. Nearly 70 percent of the expanded HE institutions in India today are promoted by the private sector. This apart, the recent years also reveal a staggering enrolment in Indian universities and a steep climb in GER from 8.1 per cent in 2001-02 to 26.3 per cent (AISHE 2019-20).